A Different Risk–Return Relationship - Aydin Selim Oksoy; Matthew R. Farrell; Shaomin Li (Risks)
We challenge the widely accepted premise that the valuation of an early-stage firm is simply the capital invested (USD) divided by the equity received (%). Instead, we argue that this calculation determines the break-even point for the investor; for example, investing USD 1.0 in exchange for a 10% equity sets a firm-level free cash flow target of USD 10.0, resulting in a 0% return for the investor. The design of our study is that of a descriptive analysis of the phenomenon, based on three assumptions: that angel investing is a two-issue negotiation, that negotiation positions are communicated sequentially from capital to equity, and that the capital is fixed to a strategic trajectory. We note that when pausing the negotiation once a strategic trajectory (and thus capital) has been defined, utilizing the break-even point as the main reference point provides a structure that can serve as a guiding barometer for negotiators, as they evaluate their options across the full range of equity greater than 0% and less than 100%. We draw attention to the diminishing benefit of the marginal equity percentage point [diminishing at a rate of (−1/x2)] for the investor to break even on their investment. This relationship tracks to the equation [value = 1/equity], which presents the full option set for any offer, once the capital is determined. Our study provides the practitioner with the subtle benefit of situational awareness and the scholar with a logical foundation for future research.